Genomic landscape and clinical actionability of renal cell carcinoma in an Indian cohort: A real-world targeted next-generation sequencing study - Vineet Talwar; Arpit Jain; Varun Goel; Bhumi Agarwal; Prateek Gupta; Rupal Tripathi; Sudhir Rawal; Anurag Mehta (World Journal of Clinical Oncology, 2026)
BACKGROUND Renal cell carcinoma (RCC) demonstrates extensive genomic heterogeneity. While major sequencing projects like The Cancer Genome Atlas have defined key molecular causes; real-world genomic data from Indian population is limited. This study intends to define the mutational landscape of RCC in an Indian tertiary cancer center and to evaluate the clinical actionability of identified alterations using the European Society for Medical Oncology Scale for Clinical Actionability of Molecular Targets (ESCAT). AIM To characterize the genomic landscape of RCC in an Indian real-world cohort using targeted next-generation sequencing (NGS) and to evaluate the clinical actionability of detected alterations according to the ESCAT. METHODS This retrospective real-world investigation included 48 patients with pathologically diagnosed RCC who underwent tumor genomic profiling with a focused 14-gene NGS panel encompassing chromatin-remodeling genes, DNA damage repair (DDR) pathways, and the PI3K-AKT-mTOR signaling axis. Clinicopathological features were collected and genetic changes were categorized by ESCAT tiers to assess potential clinical significance. RESULTS The cohort comprised 75% males with a median age of 58 years. Clear cell RCC (ccRCC) was the most common histology (81.3%) and advanced disease (American Joint Committee on Cancer stage III/IV) was found in 56.2% of patients. The most frequently altered genes were VHL (35.4%), PBRM1 (25.0%), SETD2 (14.6%), ATM (12.5%), and TP53 (12.5%). In the ccRCC subgroup (n = 39), mutation frequencies for VHL and PBRM1 were 38.5% and 25.6%, respectively. The most prevalent co-alteration pattern was VHL-PBRM1 mutations (n = 6). ESCAT analysis showed potentially actionable alterations in 18.8% of cases, mostly Tier II/III variants in the PI3K-AKT-mTOR pathway (MTOR, TSC1/TSC2, PIK3CA) and Tier III/IV alterations in DDR genes. CONCLUSION This study delineates the real-world genomic landscape of RCC in an Indian cohort, confirming key chromatin-remodeling alterations characteristic of ccRCC while suggesting relatively higher frequencies of ATM and TP53 mutations. Although targeted NGS provides important molecular insights, the proportion of high-tier actionable alterations remains limited, underscoring the need for broader genomic profiling and biomarker-driven studies in this population.